2020
DOI: 10.20524/aog.2020.0459
|View full text |Cite
|
Sign up to set email alerts
|

How to increase proximal adenoma detection rate: a meta-analysis comparing water exchange, water immersion and air/CO2 insufflation methods for colonoscopy

Abstract: BackgroundRecent meta-analyses have demonstrated a higher adenoma detection rate using the water exchange method (WE), compared to water immersion (WI) and air/CO 2 insufflation (ACI). Proximal adenomas have a high miss rate owing to their location and appearance. We performed a systematic review and meta-analysis of studies comparing the WE and WI methods to the ACI method, with a primary focus on proximal adenoma detection rate. MethodsThe following databases were searched for our systematic review: Medline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(78 reference statements)
0
10
0
Order By: Relevance
“…Various newer modalities have been studied to help increase ADR. Some of these interventions include changes in procedure techniques like water immersion and water exchange, add-on devices like Endo-Cuff, cap-assisted colonoscopy, image enhancement with narrow-band imaging (NBI) or chromoendoscopy 29 30 31 32 and DNN based computer learning capabilities. While AIAC has shown promising results in improving ADR in the recent RCTs, it is unclear if the impact is significant enough to warrant changes in clinical practice.…”
Section: Characteristics and Quality Of The Studiesmentioning
confidence: 99%
“…Various newer modalities have been studied to help increase ADR. Some of these interventions include changes in procedure techniques like water immersion and water exchange, add-on devices like Endo-Cuff, cap-assisted colonoscopy, image enhancement with narrow-band imaging (NBI) or chromoendoscopy 29 30 31 32 and DNN based computer learning capabilities. While AIAC has shown promising results in improving ADR in the recent RCTs, it is unclear if the impact is significant enough to warrant changes in clinical practice.…”
Section: Characteristics and Quality Of The Studiesmentioning
confidence: 99%
“…Numerous interventions have been introduced to improve the ADR of colonoscopy. These include the use of add‐on devices (endocap, endoring, endocuff, G‐EYE, and amplifEYE), electronic chromoendoscopy (narrow band imaging, linked color imaging, blue laser imaging, and flexible spectral imaging color enhancement), water‐aided techniques (water immersion and water exchange), use of second observer, antispasmodic administration, retroflexion in the right colon or second forward view, quality control initiatives, and improved bowel preparation . However, there are still a number of adenomas that are missed during colonoscopy, and current efforts are being directed to prevent this.…”
Section: Introductionmentioning
confidence: 99%
“…The U.S. Multi-Society Task Force set ADR benchmarks of ≥ 25 % overall (≥ 20 % in women and ≥ 30 % in men) among colonoscopists to achieve high-quality examinations [29]. Numerous interventions and techniques including use of distal attachments (cap, cuff, rings), virtual chromoendoscopy, water-based techniques, having a second observer, premedication with peppermint oil, optimizing bowel prep and ensuring good examination techniques have been proposed previously to improve ADR during colonoscopy [12,13,[30][31][32][33][34]. Our study demonstrated the potential use of i-scan with surface and CE as an additional modality that can be employed to improve the ADR [22,35].…”
Section: Discussionmentioning
confidence: 99%